(3CSGSjGJ GdJfXje hGdGOGQI (B/s - (3CHh bMa, YHO GdSdGes ((3GdGScfOQjI(B: s (3OGQ GdeYQaI GdLGeYjI(B, s, 2001)
(3GdJNWjW, GdJfXje, GdJhLjg, GdQbGHI hJbjje GdGOGA, GOGQI GdGYeGd GdOhdjI, fXe GdeYdheGJs
Keywords: (3GdGOGQI, GdJNWjWs; (3GdQbGHI, fXe GdeYdheGJs